Pelembutan Citra dengan Metode Filter Gaussian - Junaidy B Sanger; Immanuela P. Saputro P. Saputro; Yunita Komalig (Journal of Electrical Engineering and Computer (JEECOM), 2023)
Image is a multimedia component rich in information and has an essential role as an information provider. However, the images encountered often experience a decrease in quality, such as defects or noise, causing the information conveyed from these images less clear. Noise causes the image to be too contrasted, blurry, or not sharp enough. One type of noise is contrast noise. Image Smoothing here is one of the operations to improve quality which aims to smooth out images with unbalanced contrast noise. Disturbances in the image are generally in the form of variations in the intensity of a pixel that is not correlated with neighboring pixels. Contrasting images are caused by uneven lighting, which can cause the information in the image to be reduced and difficult to interpret. For this reason, quality improvement must be made to get a better image. In this study, the softening of contrasting images uses the Gaussian Filter method. This filter has the effect of equalizing the gray distance to make the image obtained smoother. Based on the results of the tests, it got an accuracy of 83.3%, meaning that the application's performance is suitable for image smoothing.